739 Atypical presentation of Takotsubo syndrome early after pacemaker implantation. (8th December 2021) - Demurtas, Elisabetta; Restelli, Davide; Parisi, Francesca; Allegra, Marta; Procopio, Cristina; Pistelli, Lorenzo; Crea, Pasquale; Dattilo, Giuseppe; Luzza, Francesco; Micari, Antonio; Carerj, Scipione; Di Bella, Gianluca
Abstract: Aims: Takotsubo syndrome (TTS) is an acute stress-induced cardiomyopathy showing left ventricular (LV) dysfunction without obstructive coronary arteries disease. A sudden massive surge of circulatory catecholamines from an intense physical or emotional stress may play a central role in the pathogenesis of TTS. We report the case of an 87 years-old woman who developed TTS with uncommon presentation after permanent pacemaker (PM) implantation. Methods and results: The patient was referred to our hospital for PM implantation because of advanced atrio-ventricular block (3:1). She suffered by rheumatoid arthritis (RA), arterial hypertension, and chronic kidney disease. Echocardiogram, performed before PM implantation, showed normal LV kinesis and normal ejection fraction (EF 60%). She was initially administered with infusion of Isoprenaline 2 mcg/min. The subsequent day, she underwent permanent dual-chamber pacemaker implantation without any complications. After 3 days, the patient complained severe asthenia and fever, together with increase of white blood cells and C reactive protein. Blood cultures were negative. We started antibiotic therapy and, suspecting a reactivation of RA, steroid therapy with infusion of methylprednisolone 40 mg/die. Electrocardiogram showed normal sinus rhythm and paced ventricular rhythm. PM interrogation showed normal function. Surprisingly, echocardiogram showed LV dysfunction with apical and medium segments akinesia, and severe EF reduction (35%). Coronary angiography documented absence of coronary obstructive lesions, assessing diagnosis of TTS. The patient was discharged 1 week after admission in good clinical condition. One week later, an echocardiogram showed apical akinesia, partial recovery of medium segments motility, and slight increase of EF (40%). The excess of catecholamines could lead to decreased cardiac muscular function and to spasm of coronary arteries: these events can lead to acute heart failure and decrease of LVEF. Furthermore, about 90% of patients with TTS are women, especially in postmenopausal period. Peculiarities of this case were the atypical symptoms of TTS and the combination of different predisposing stressors factors: female sex in postmenopausal period, anamnesis of chronic inflammatory disease, use of stress-inducing drugs (methylprednisolone and isoprenaline, the last associated with TTS after PM-implantation), atrio-ventricular block itself, and PM implantation procedure. Our findings remark that even a low-risk procedure could be a possible cause of TTS in patient with such risk factors. In our opinion, in this subset of patients, conscious sedation could be useful to reduce the stress load, together with an early procedure and consequently the minimal use of exogenous stress drugs like Isoprenaline, even if the patient is in a good clinical condition. Conclusions: This case highlights TTS as a potential complication after PM implantation, especially in post-menopausal women with high pre-existing stress load.